Modelling primary blast lung injury: current capability and future direction. Issue 2 (23rd November 2016) - Scott, Timothy; Hulse, E; Haque, M; Kirkman, E; Hardman, J; Mahoney, P
Abstract : Primary blast lung injury frequently complicates military conflict and terrorist attacks on civilian populations. The fact that it occurs in areas of conflict or unpredictable mass casualty events makes clinical study in human casualties implausible. Research in this field is therefore reliant on the use of some form of biological or non-biological surrogate model. This article briefly reviews the modelling work undertaken in this field until now and describes the rationale behind the generation of an in silico physiological model.